IDEOLOGY OF DISASTER EDUCATION TRAUMA HANDLING POST-EARTHQUAKE IN PICTURE STORIES BOOK: CRITICAL DISCOURSE ANALYSIS - Damayanti, Silvia; Suarka, I Nyoman; Banda, Maria Matildis; Purnawati, Ketut Widya (UI Scholars Hub, 2024)
This research analyzes the ideology that the author intends to instill in picture storybooks for children in Japan. The study aims to explore how the author conveys the ideology of handling trauma in children after earthquake disasters. The objects of the study are two picture storybooks titled